Phosphatidylinositolphosphate phosphatase activities and cancer - Rudge, Simon A; Wakelam, Michael J O (Journal of lipid research, 2016)
Signaling through the phosphoinositide 3-kinase pathways mediates the actions of a plethora of hormones, growth factors, cytokines, and neurotransmitters upon their target cells following receptor occupation. Overactivation of these pathways has been implicated in a number of pathologies, in particular a range of malignancies. The tight regulation of signaling pathways necessitates the involvement of both stimulatory and terminating enzymes; inappropriate activation of a pathway can thus result from activation or inhibition of the two signaling arms. The focus of this review is to discuss, in detail, the activities of the identified families of phosphoinositide phosphatase expressed in humans, and how they regulate the levels of phosphoinositides implicated in promoting malignancy.